Challenges of Small and Medium Enterprises to Meet the Requirements of Industrial Revolution 4.0 in Vietnam - Nghia, Nguyen Trong; Hanh, Le Thi; Dung, Nguyen Huu (International Journal of Multidisciplinary in Management and Tourism, 2020)
Industry 4.0 is a term for the digital revolution in industrial production emerging from the comprehensive networking and computerisation of all areas of production. The changes arising from the digital revolution in the pro-duction and value creation process are radical and pose a real challenge to enterprises. In order not to be left behind companies need to develop strategies in good time to ex-ploit the new possibilities of digitalisation, to improve estab-lished processes and develop new business models. The increasing involvement of Vietnam in international organizations and forums requires each enterprise to have appropriate strategies to adapt to the new business environment to meet the requirements of the Industrial Revolution. 4.0. Small and medium enterprises are now the majority of enterprises, and are an important part of the production of gross domestic product. The constant change and movement of the economy has created many conditions for small and medium enterprises to expand production and business development, while also bringing many difficulties and challenges. Therefore, the author examines the challenges that small and medium enterprises meet the Industrial Revolution 4.0 to provide a new perspective to help small and medium enterprises overcome difficulties to develop sustainably, contributing to the overall growth of the economy.